Topology and quantum theory in interaction: NSF-CBMS Regional Conference in the Mathematical Sciences on Topological and Geometric Methods in QFT, July 31-August 4, 2017, Montana State University, Bozeman, Montana - Ayala, David; Freed, Daniel S.; Grady, Ryan (Contemporary mathematics, 2018)
Geometry and physics: an overview / David R. Morrison -- An introduction to spin systems for mathematicians / Ingmar Saberi -- The Arf-Brown TQFT of pin⁻ surfaces / Arun Debray and Sam Gunningham -- A guide for computing stable homotopy groups / Agnes Beaudry and Jonathan A. Campbell -- Flagged higher categories / David Ayala and John Francis -- How to derive Feynman diagrams for nite-dimensional integrals directly from the BV formalism / Owen Gwilliam and Theo Johnson-Freyd -- Homotopy RG flow and the non-linear -model / Ryan E. Grady and Brian Williams -- The holomorphic bosonic string / Owen Gwilliam and Brian Williams
Includes bibliographical references
Keywords: Konferenzschrift -- 31.07.2017.04.08.2017 -- Bozeman, Montana